Experiencia de la adaptación del método de Glenn Doman en los procesos de enseñanza aprendizaje del lenguaje oral - Posada Gallego, Isabel Cristina (Educación, 2017)
This document is a research to get a Bachelor degree in Preschool Education, which proposes to systematize the experiences of the Glenn Doman Method adaptations with one year old children from Carrizales Preschool in Envigado. It focuses on teaching and learning strategies in oral language acquisition and aims to answer to what extend the method adaptation experiences could improve this process in learners.